Pemodelan Posisi Akses Poin Jaringan Wifi Jurusan Teknik Elektro Universitas Negeri Padang - Nevi Faradina; Dwiprima Elvanny Myori (JTEV (Jurnal Teknik Elektro dan Vokasional), 2022)
Aware of the importance of an internet connection today, UNP has facilitated an internet wifi network to support the needs of academic, non-academic staff, and students. This wifi network can be enjoyed throughout the campus environment including the electrical engineering department which is connected through several hotspots throughout the campus. However, the strong network signal is considered unstable and not evenly distributed to serve all civitas, especially for the students. In some places, the signal level received is very weak. While in other locations, the user did not get a signal or better known as the blankspot. This is due to the fact that the installed access points are not optimal, both in terms of number and in the position of its installation. Access points positioning by providing certain conditions can also be made so that signal build-up in one area and blankspot conditions in other areas can be avoided. For this reason, it is necessary to analyze, calculate and plan the position of the access point before the tool is installed. To calculate the exact number of access points, it is necessary to estimate the number of daily bandwidth requirements in the electrical engineering department. Then calculate the number of access points both in terms of capacity and coverage. Last, a simulation will be carried out so that the best access point installation position will be obtained.